2019
DOI: 10.1101/822726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-genome duplication and host genotype affect rhizosphere microbial communities

Abstract: The composition of complex microbial communities found in association with plants is influenced in part by host phenotype. Yet, the salient genetic architecture is often unknown. Genome duplication events are common in the evolutionary history of plants, influence many important plant traits, and may affect associated microbial communities. Using experimentally induced whole genome duplication (WGD), we tested the effect of WGD on rhizosphere bacterial communities in Arabidopsis thaliana. Specifically, we perf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Likewise, we did not find any significant differences in the relative abundance of any of the synthetic community members across the two ploidy levels, both of which were dominated by Pantoea, Pseudomonas, and Exiguobacterium. This is in line with work on wheat, where ploidy was found to play a weak and inconsistent role in shaping the below-ground microbiome (Wipf & Coleman-Derr 2021), but contrasts with previous work on Arabidopsis which did find a signature of ploidy in shaping microbial community composition across accessions (Ponsford et al 2020).…”
Section: Effects Of Polyploidy On Microbiome Diversitysupporting
confidence: 83%
“…Likewise, we did not find any significant differences in the relative abundance of any of the synthetic community members across the two ploidy levels, both of which were dominated by Pantoea, Pseudomonas, and Exiguobacterium. This is in line with work on wheat, where ploidy was found to play a weak and inconsistent role in shaping the below-ground microbiome (Wipf & Coleman-Derr 2021), but contrasts with previous work on Arabidopsis which did find a signature of ploidy in shaping microbial community composition across accessions (Ponsford et al 2020).…”
Section: Effects Of Polyploidy On Microbiome Diversitysupporting
confidence: 83%
“…These results regarding ploidy effects on bacterial recruitment loosely corroborate past work in which a cordgrass allopolyploid (genus Spartina ) was found to harbor a more diverse rhizosphere bacterial community, as compared to diploid counterparts [ 64 ]. Another study using Arabidopsis reported that rhizosphere community composition—but not alpha diversity—shifted with whole genome duplication and differences in host genotype [ 65 ]. Indeed, degree of impact from host genetic factors, including ploidy level, on the plant microbiome seems to vary across species, as observed in our cotton outgroup compared to tested wheat species, as well as demonstrated in past work [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Or is it a contributing mechanism of hybrid vigor itself? These questions could be addressed using synthetic microbial communities, reinoculation or soil‐conditioning experiments (Panke‐Buisse et al ., 2015; Vorholt et al ., 2017; Ponsford et al ., 2019). These important next steps will help to clarify the role of plant‐associated microbes in hybrid vigor.…”
Section: Discussionmentioning
confidence: 99%